MAGMATIC NI-CU VERSUS PGE DEPOSITS: CONTRASTING GENETIC CONTROLS AND EXPLORATION IMPLICATIONS - Li C.; Maier W.D.; De Waal S.A. (My University, 2001)
Both Ni-Cu and PGE deposits are associated with mafic and ultramafic rocks, but the former often occur in dynamic magmatic systems such as lava channels and magma conduits whereas the later occur in larger layered intrusions. The contrasting modes of occurrence appear to be related to different degrees of preferential partitioning of the metals (PGE versus Cu and Ni) into segregating sulfide liquid and different concentration processes of the sulfide liquid during the formation of the ores. Primary magmas derived from partial melting of the upper mantle are fertile in PGE, Ni and Cu only when the molten sulfides are completely dissolved in the magmas. This requires a high degree of partial melting of the mantle, perhaps higher than 30 percent. The partial melts usually have basaltic to komatiitic compositions, and are unlikely to achieve sulfide saturation during ascent to the crust. Fractional crystallization and crustal contamination are the most important processes known to have induced sulfide saturation in magma upon intrusion. Sulfide liquid segregated in a large chamber may achieve high R-factors required for the formation of reef-type PGE deposits. Crustal assimilation appears to be most effective in dynamic lava channels and magma conduits. A large volume of sulfide liquid segregated from magma in such dynamic environments often has a lower R-factor, and relatively lower metal concentrations. Such metal-poor sulfide liquid needs to be deposited in restricted localities, and/or to be upgraded in metals by reacting with new surges of magma, to become a Ni-Cu sulfide deposit. Because of their extremely high partition coefficient between sulfide liquid and magma, PGE will become significantly depleted in magma even at small amounts of sulfide segregation. Copper, on the other hand, will be much less depleted because of its relatively low partition coefficient. Thus, Pd/Cu ratios in whole rocks can be used to detect PGE mineralization associated with small sulfide segregation in large layered intrusion. The whole rock Cu/Zr ratio is sensitive to large amounts of sulfide liquid segregation from magma and thus is a useful tool for Ni-Cu exploration. Nickel contents of olivine can also be used to identify Ni depletion in magma associated with large amounts of sulfide segregation.